1993
DOI: 10.1159/000266206
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Speech after Completed Late Closure of the Hard Palate

Abstract: Speech was analyzed about 1 year postoperatively in 30 patients with cleft lip and palate who were the first ones to undergo late closure of the hard palate in Gothenburg, Sweden. Fourteen had bilateral and 16 had unilateral clefts. Soft palate closure had been performed at the mean age of 8 months, and the hard palate was closed at the mean age of 8 years with a range of 7–11 years. Imitated and spontaneous speech was analyzed at an average of 15 months after palatal repair. Six percent had moderate to severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 5 publications
0
6
2
Order By: Relevance
“…This prevalence was higher than those found in previous studies [8,27,37,38], where the prevalence of resonance disorders or VPI ranged from 20% to 30%. Voice disorders were found in 8 of 42 children (19%) and this was in range of prevalence of 0 to 47% found previously [4,39,40].…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…This prevalence was higher than those found in previous studies [8,27,37,38], where the prevalence of resonance disorders or VPI ranged from 20% to 30%. Voice disorders were found in 8 of 42 children (19%) and this was in range of prevalence of 0 to 47% found previously [4,39,40].…”
Section: Discussioncontrasting
confidence: 72%
“…Late palatoplasty is considered to produce a better result for speech outcomes [2][3][4] and less maxillary growth restriction [5][6][7]. The incidence of compensatory articulation disorders (CAD), hypernasality (moderate to severe), and voice disorders (because of hyperfunctional compensation) were 23%, 6%, and 43%, respectively in children with a cleft palate who received late palatoplasty (veloplasty at 8 months and closure of hard palate at 8 years) [8]. Children with delayed closed clefts had significantly more nasal escape and a higher prevalence of compensatory retracted articulation than children with functionally closed clefts [9].…”
Section: Doi: 105372/1905-74150806347mentioning
confidence: 99%
“…The phonetic analysis of consonant production revealed three types of articulation errors in both the Furlow and WardillKilner group: incorrect production of the trill sound /r/ and the fricative /s/, and devoicing of /z/, /v/, /g/, and /d/. S-like deviations were also mentioned in the study by Lohmander-Agerskov and Söderpalm [26]. Also Grunwell et al [27] reported in their cross-linguistic investigation, distortions of the /s/ sound.…”
Section: Discussionmentioning
confidence: 65%
“…The phonetic analysis of consonant production revealed three types of articulation errors: incorrect production of the trill sound /r/ and the fricative /s/, and devoicing of /z/, /v/ and /d/. S-like deviations were also mentioned in the studies by Lohmander-Agerskov and Söderpalm [3] and Grunwell et al [6]. No other study reported misarticulations of /r/ and the presence of devoicing.…”
Section: Discussionmentioning
confidence: 89%
“…Statistically significant nasality differences regarding the Bzoch test and the Glatzel test were found between the non-cleft normative data [27] and the group of cleft palate subjects. Also in the studies by Lohmander-Agerskov and Sö-derpalm [3], Riski [5] and Grunwell et al [6] the presence of hypernasality was suggested. In contrast with the above-mentioned investigations no other types of nasality disorders were observed during spontaneous speech.…”
Section: Discussionmentioning
confidence: 99%